Microvasculature Features of Vogt-Koyanagi-Harada Disease Revealed by Widefield Swept-Source Optical Coherence Tomography Angiography - Ye, Xiaoyuan; Zhang, Haiping; Xiao, Peng; Wang, Gengyuan; Hu, Xiaoqing; Yan, Chun; Li, Fan; Hu, Yixin; Su, Lishi; Luo, Jiawen; Yuan, Jin; Wen, Feng; et al. (Frontiers in Medicine, 2021)
Background: Vogt-Koyanagi-Harada (VKH) disease is a multisystem autoimmune disorder which could induce bilateral panuveitis involving the posterior pole and peripheral fundus. Optical coherence tomography angiography (OCTA) provides several advantages over traditional fluorescence angiography for revealing pathological abnormalities of the retinal vasculature. Until recently, however, the OCTA field of view was limited to 6 × 6 mm2 scans. Purpose: This study examined retinal vasculature and choriocapillaris abnormalities across multiple regions of the retina (15 × 9 mm2 wide field, macula, peripapillary regions) among acute and convalescent VKH patients using a novel widefield swept-source OCTA (WSS-OCTA) device and assessed correlations between imaging features and best-corrected visual acuity (BCVA). Methods: Twenty eyes of 13 VHK disease patients in the acute phase, 30 eyes of 17 patients in the convalescent phase, and 30 eyes of 15 healthy controls were included in this study. Vascular density (VD) in superficial and deep vascular plexuses (SVP, DVP), vascular perfusion density (VPD) in SVP, DVP, and choriocapillaris (CC), and flow voids (FVs) in CC were measured across multiple retinal regions via WSS-OCTA (PLEX Elite 9000, Carl Zeiss Meditec Inc., USA) using the 15 × 9 mm2 scan pattern centered on the fovea and quantified by ImageJ. Results: Compared to healthy controls, acute phase VKH patients exhibited significantly reduced SVP VD, SVP VPD, and CC VPD across multiple retinal regions (all p<0.01). Notably, the FV area was more extensive in VKH patients, especially those in the acute phase (p<0.01). These changes were reversed in the convalescent phase. Strong negative correlations were found between logMAR BCVA and macular DVP perfusion measures during the acute phase (VD: r=-0.585, p<0.01; VPD: r=-0.457, p<0.05). While during the convalescent phase, there were positive correlations between logMAR BCVA and macular FV measures (FV area: r=0.466; FV average size: r=0.487, both p<0.001). Conclusion: The wider field of SS-OCAT provides more comprehensive and detailed images of the microvasculature abnormalities characterizing VKH disease. The quantifiable and layer-specific information from OCTA allows for the identification of sensitive and specific imaging markers for prognosis and treatment guidance, highlighting WSS-OCTA as a promising modality for the clinical management of VKH disease.